OCHRONA ADMINISTRACYJNA PRAWA DO INFORMACJI O CHARAKTERZE PUBLICZNYM - Piskorz-Ryń, Agnieszka (Wydział Prawa i Administracji UAM, 2007)
The paper presents the basic means of administrative and judicial control exercised over the access to information contained in public records in various legal systems, with particular emphasis put on the role o f independent administrative entities appointed to supervise access to that information. Further in the text, the solutions adopted in the Polish Public Information Access Act are presented and an attempt o f their evaluation is offered. Such an evaluation, however, cannot be made without referring to the basic issue, i.e. the choice of the model of administrative control over the right to information contained in public records. Thus, the paper presents arguments in favour o f establishing a specialised entity authorised to manage the access to public information in Poland, and arguments against such a proposal. Basing on the analysis of other states’ experience, the author supports the idea of establishing a specialised, consultative information protection authority in Poland.
ADMINISTRATIVE CONTROL OF THE RIGHT TO INFORMATION CONTAINED IN PUBLIC RECORDS